2022
DOI: 10.1002/jobm.202200106
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of Pseudomonas sp. A46 isolated from mercury‐contaminated wastewater

Abstract: Pseudomonas sp. A46 was first isolated from mercury-contaminated groundwater in Taiwan. This study is the first to report the draft whole-genome sequence of Pseudomonas sp. A46. Its genome consists of 126 contigs, with a total length of 6,782,516 bp and a GC content of 64.7%. Phylogenetic analysis based on 16 S rRNA gene sequences revealed that Pseudomonas sp. A46 is closely related to Pseudomonas citronellolis. Assessment of the draft genome sequence revealed that Pseudomonas sp. A46 harbors sets of genes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…The copG gene in both genomes encoded a copper amine oxidase, which was responsible for copper resistance as well [ 87 ]. Both strains were potentially tolerant of the mercury ions due to two different mechanisms: MerA enzyme is a widespread mercuric ion reductase (EC: 1.16.1.1), which is highly expressed under mercury stress in a number of prokaryotic organisms [ 88 , 89 , 90 ]; and ZntA protein is a lead-, cadmium-, zinc-, and mercury-transporting ATPase, which is found in phylogenetically closely related bacteria of the Ensifer / Sinorhizobium clade as well [ 8 , 91 ]. Finally, tolerance of the isolated strains to the chromium ions was possible due to the presence of the chrAF genes responsible for chromate transport (ChrA is a chromate efflux transporter) in their genomes [ 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…The copG gene in both genomes encoded a copper amine oxidase, which was responsible for copper resistance as well [ 87 ]. Both strains were potentially tolerant of the mercury ions due to two different mechanisms: MerA enzyme is a widespread mercuric ion reductase (EC: 1.16.1.1), which is highly expressed under mercury stress in a number of prokaryotic organisms [ 88 , 89 , 90 ]; and ZntA protein is a lead-, cadmium-, zinc-, and mercury-transporting ATPase, which is found in phylogenetically closely related bacteria of the Ensifer / Sinorhizobium clade as well [ 8 , 91 ]. Finally, tolerance of the isolated strains to the chromium ions was possible due to the presence of the chrAF genes responsible for chromate transport (ChrA is a chromate efflux transporter) in their genomes [ 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…At this level of genus, Pseudomonas, Nocardioides, Pseudonocardia, and Pseudarthrobacter are the dominant microbial communities. It has been shown that these bacteria have good resistance to heavy metals, that they coexist well with heavy metals, and that these bacteria are often isolated in a variety of environments heavily contaminated with heavy metals [72,77,78]. In addition, other studies have shown that Pseudarthrobacter is not only enriched in heavy metal-contaminated environments, but also plays a key role in promoting plant growth, and therefore, this bacterium also has great potential for application in bioremediation at VTM mining sites [79,80].…”
Section: Microbial Community Responsesmentioning
confidence: 99%